Смртноста кај пациенти со акутна бубрежна инсуфициенција (5 годишен клинички материјал) - Трајковски, Владимир (Faculty of Medicine, UKIM, Skopje, Macedonia, 1999)
The acute renal failure (ARF) represents a syndrome of multi-etiological origin that can be defined as a rapid impairment of the renal excretory function, with reduction of the glomerular filtration rate (GFR) and retention of the degradation products of nitrogen metabolism (urea, creatinine, indol, scatol, phenol, succinyl guanidine acid…). The aim of this master theses is: to present the mortality rate in ARF patients, to determine the influence of the demographic factors upon the outcome, to get an insight in the etio-pathogenetic factors with lethal outcome, to analyze multiorganic damages in correlation with outcome, to establish relation between laboratory parameters and mortality of the syndrome, to compare therapeutic procedures and to present survival rate of patients with ARF. The clinical material of patients affected by ARF hospitalized in the Department of Nephrology – Skopje, in the period 01.01.1990 – 31.12.1994 was used in this study. The study is retrospective, descriptive - epidemiological. Hundred and fifteen patients were analyzed and divided in two groups: 27 dead and 88 survived. A clinical-epidemiological approach was used in processing the results. The statistic analysis of the data derived by the following methods: dynamic indexes, Pearson’s X2 test, Kolmogorov-Smirnov test was used. Continuing variables were analyzed by Student’s t-test or analysis of variances (ANOVA). Also, a simple and multiple regression analysis was used for selection of most important factors-predictors for higher mortality rate. Conclusion of the analysis was that the mortality rate was 23,5%. By demographically factors only the older group has a role of a predictor for lethal outcome. It was stated that the duration of the hospitalization has the significance as a factor associated with the condition upon admission of the patient, and better results were reached by the treatment. Out of the etiologic modalities, the medical ARF was distinctive with mortality rate of 25,3%. Main reason for lethal outcome is a cardiogenic shock and heart failure up to 100%. The mortality from surgical reasons is 22,7% and gynecological ARF has 14,3% mortality. A strong positive correlation is established (r=0.93) between multiorgan system failure (MOSF) and mortality. By multivariate analysis, a positive correlation was established between the lethal outcome and the duration of hospitalization (p<0.01), wound infection (p<0.04) and the age of patients (p<0.02). Univariate analysis showed association between mortality with ARF and the following variables: comma on admission, the need of assisted mechanical ventilation and existence of abdominal infections. DIC syndrome affects the mortality (p<0.05). Out of the laboratory parameters the following were found significant: the number of leukocytes (p=0.01), platelets (p=0.05), glycemia (p=0.01) and the enzyme GGT (p=0.05). Patients treated with hemodialysis have a significantly higher mortality when compared to the ones treated in conservative manner (p=0.05), which is due to the severity of the underlying disorder. The survival rate is 76.5%. Undertaking preventive and therapeutic measures to avert the passage from prerenal into intrinsic ARF can be of particular importance for a decrease in the mortality of ARF.
Mortality in patients with acute renal failure (5 years clinical material)
Владимир Трајковски го одбрани магистерскиот труд на 19.03.1999 година на Клиниката за нефрологија при Медицински факултет во Скопје. Комисија: 1. Проф. д-р Кочо Чакалароски, 2. Проф. д-р Ристо Гроздановски, 3. Проф. д-р Блаже Николовски
Keywords: acute renal failure (ARF), mortality, outcome, multiple organ system failure (MOSF)